Pengaruh Interaksi Genotipe dan Lingkungan terhadap Hasil Kacang Hijau - Trustinah, Trustinah; Iswanto, Rudi (Jurnal Penelitian Pertanian Tanaman Pangan, 2013)
Genotype x Environment Interaction (GEI) is a common phenomena, causing differences in grain yield ranking of genotypes among environments. Identification of genotypes that are stable and adaptive to specific environment is important in cultivar development. Nineteen mungbean genotypes were tested at 8 locations, namely Ngawi, Demak, and Probolinggo in dry season of 2011, and Ngawi, Demak, Probolinggo, Gresik and Lamongan in dry season of 2012. The trial was arranged in a randomized block design with three replications. Each genotype was planted on plot size of 4 m x 4 m (10 rows, 4 m long), with a spacing of 40 cm x 10 cm, two plants/hill. The data were analyzed using the MSTAC program. Analyses on genotype x environment interaction, stability, and adaptability were done referring to Eberhart and Russell (1966), while biplot analyses were done using the AMMI program. The effect of genotype x environment interaction, and the genotype x environment (linear) interaction which was significant to yield were important in determining the yield stability of mungbean genotypes. Locations contributed the highest to the total variance (71.7%), followed by genotype x environment interaction (25.1%). The average yields of the mungbean genotypes at eight locations ranged from 1.25 to 2.15 t/ha, and the average yield across locations of each mungbean genotype ranged from 1.59 to 1.80 t/ha. Two lines were considered as stable genotypes and with high yields, namely G12 and G17. Genotypes G5 and G6 were stable and adapted to optimal environment, while G4 was adapted to sub-optimal environment. All genotypes were considered stable based on both AMMI also stable on regression techniques.